THE RESEARCHING EFFECTS OF ELECTRODE MATERIAL TO THE POSSIBILITY CREATING PLASMA AND DEGRADABLE ABILITY OF 2,4-DICHLOROPHENOXYACETIC ACID IN WATER ENVIRONMENT - Công (Journal of Military Science and Technology, 2021)
The plasma discharge process creates free radicals OH•, H•, O• and active species such as O, H, O2, H2, H2O2. These were agents that had strong redox potential, when reaction with toxic organic molecules in water solution or air environment, they easily decomposed these hazard organic compounds into non-toxic substances. This paper present the influence of Fe, Cu, W electrode material on the decomposition of 2,4-Dichlorophenoxyacetic acid in water environment. The researching results show that the decomposition efficiency for 2,4-D solution concentration of 30 mg/L, the reaction durating time of 60 minutes on the iron, copper, vonfram electrodes reached at 67.13%; 49.76%; 29.24%, respectively. Thus, it can be seen that the decomposition of 2,4-D by plasma and combining with Fenton reaction on Fe electrode get the highest degradation efficiency.